Comparative Study of Land Registration in the State of the Republic of Indonesia and the Republic of Singapore - Jayanti, RA Andria; Arba, M; Hirsanuddin, Hirsanuddin (Faculty of Law, Khairun University, 2017)
This research aims to compare the value of certainty and protection of protection of land law in Indonesia and Singapore which aims to provide certainty and legal protection. This type of legal research is normative legal research. The method of approach used is legislation, conceptual and comparative approach. Based on the research that is registration of land in Indonesia is regulated in Law of the Republic of Indonesia Number 5 Year 1960 Article 19 BAL (Basic Agrarian Law/ Undang-Undang Pokok Agraria), and in Singapore regulated in Land Titles Act (LTA) Chapter 157 Year 2015. There are similarities and differences in registration of land, among others, Indonesia and Singapore adopt the right registration system (Torrens). Indonesia adopts negative publication of positive tendency system that produces certificate as a strong evidence and existence of rechtsverwerking institution (Government Regulation of the Republic of Indonesia Number 24 Year 1997 Article 32) while in Singapore adopt positive publication system that generates certificate as absolute proof (LTA 157 Year 2015 Article 36) and the presence of caveat as a form of legal protection. It is expected that by changing the registration of land law in Indonesia can provide absolute legal certainty and legal protection in registration of land as in Singapore.